Zein/gelatin/nanohydroxyapatite nanofibrous scaffolds are biocompatible and promote osteogenic differentiation of human periodontal ligament stem cells. (1st March 2019) - Ou, Qianmin; Miao, Yingling; Yang, Fanqiao; Lin, Xuefeng; Zhang, Li-Ming; Wang, Yan
Abstract : In bone tissue engineering, it is important for biomaterials to promote the osteogenic differentiation of stem cells to achieve tissue regeneration. Abstract : In bone tissue engineering, it is important for biomaterials to promote the osteogenic differentiation of stem cells to achieve tissue regeneration. Therefore, it is critical to develop biomaterials with excellent cytocompatibility and osteoinductive ability. In our previous study, we found a zein/gelatin electrospinning scaffold with good biocompatibility, but low osteoinductive ability for human periodontal ligament stem cells (hPDLSCs). Therefore, herein, we fabricated novel zein/gelatin/nanohydroxyapatite (zein/gelatin/nHAp) nanofibrous membranes to overcome the drawbacks of the zein/gelatin scaffold. The results showed that the surface wettability of the zein/gelatin/nHAp nanofiber membranes was increased. Moreover, the inclusion of nHAp facilitated the attachment, proliferation, and osteogenic differentiation of hPDLSCs. Overall, the zein/gelatin/nHAp nanofiber membranes showed good biocompatibility and osteoinductive activity for hPDLSCs in vitro and in vivo ; this suggested potential applications of these membranes in bone tissue engineering.